2009
DOI: 10.1089/ars.2009.2587
|View full text |Cite
|
Sign up to set email alerts
|

Nox5 and the Regulation of Cellular Function

Abstract: The NADPH oxidase (Nox) family of enzymes is comprised of seven members, Noxes 1-5 and the Duoxes 1 and 2. Nox5 was the last of the conventional Nox enzymes to be identified, and in comparison to its siblings, much less is known about its molecular regulation and even less regarding its functional significance. The loss of Nox5 from rodent genomes has contributed significantly to this deficit in knowledge, but recent discoveries have narrowed the gap. There are many differences between Nox5 and the other Nox i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 78 publications
1
142
0
2
Order By: Relevance
“…In blood vessels from individuals without coronary artery disease, NOX5 expression is very low, but it is substantially increased in blood vessels of individuals with the disease (24). In this study, we found that NOX5 promoter hypermethylation occurred more often in VSD myocardial tissue by methylationspecific PCR.…”
Section: Discussionsupporting
confidence: 47%
“…In blood vessels from individuals without coronary artery disease, NOX5 expression is very low, but it is substantially increased in blood vessels of individuals with the disease (24). In this study, we found that NOX5 promoter hypermethylation occurred more often in VSD myocardial tissue by methylationspecific PCR.…”
Section: Discussionsupporting
confidence: 47%
“…We verified that ET-1 increased ROS levels and activated ERK1/2 in PASMCs and that increased [Ca 2ϩ ] i was necessary for both responses. Ca 2ϩ -dependent ROS generation may be due to the action of NADPH oxidase (Nox) (18,28), since ROS generation was inhibited by the Nox inhibitor DPI; however, DPI binds nonspecifically to flavins and also inhibits other oxidases. The activation of ERK1/2 depended on increased ROS levels, since antioxidants blocked ET-1-dependent ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Nox5 is the most recently identified Nox and is unique: It is Ca 2 + sensitive, possesses a calmodulin-like domain with Ca 2 + binding sites, and does not require any Nox subunits for its activity (62,92,138,185). Nox5 was first identified in testes and spleen and, more recently, in vascular cells.…”
Section: Nox5mentioning
confidence: 99%